Inclusive Leadership in Higher Education: Strategies for Dealing with Student Diversity - Cliford Ratulangi; Raymond Piring (Universitas Nurul Jadid, 2025)
This research aims to explore inclusive leadership strategies in managing student diversity in multicultural universities in Indonesia. Using a qualitative approach based on intrinsic case studies, data were obtained through in-depth interviews, policy documentation, and participatory observation in two universities. The results show that inclusive leadership is manifested in operational actions, such as lecturer diversity training, cultural orientation programs, interfaith forums, and flexible policies that support the participation of minority students. Student diversity is not only seen as a challenge but also utilized as a pedagogical resource that encourages collaborative and innovative learning. The findings also reveal challenges to cross-cultural integration, including communication barriers, limited access to information, and gaps in institutional support. Successful leadership strategies are those that combine critical awareness, policy flexibility, and systemic psychosocial support. This research has both theoretical and practical implications, as it maps the conceptual framework of inclusive leadership within the context of Indonesian higher education and also provides practical guidance for campus managers to develop an adaptive, equitable, and sustainable diversity management system.